Regulation and modulation of biogenic amine neurotransmission in Drosophila and Caenorhabditis elegans - Rosikon, Katarzyna D.; Bone, Megan C.; Lawal, Hakeem O. (Frontiers in Physiology, 2023)
Neurotransmitters are crucial for the relay of signals between neurons and their target. Monoamine neurotransmitters dopamine (DA), serotonin (5-HT), and histamine are found in both invertebrates and mammals and are known to control key physiological aspects in health and disease. Others, such as octopamine (OA) and tyramine (TA), are abundant in invertebrates. TA is expressed in both Caenorhabditis elegans and Drosophila melanogaster and plays important roles in the regulation of essential life functions in each organism. OA and TA are thought to act as the mammalian homologs of epinephrine and norepinephrine respectively and when triggered, they act in response to the various stressors in the fight-or-flight response. 5-HT regulates a wide range of behaviors in C. elegans including egg-laying, male mating, locomotion, and pharyngeal pumping. 5-HT acts prominently through its receptors, which have various classes in both flies and worms. The adult brain of Drosophila is composed of approximately 80 serotonergic neurons, which are involved in modulation of circadian rhythm, feeding, aggression, and long-term memory formation. DA is a major monoamine neurotransmitter that mediates a variety of critical organismal function and is essential for synaptic transmission in invertebrates as it is in mammals. It is also a precursor for noradrenaline and adrenaline. In C. elegans and Drosophila as in mammals, receptors play a key role in DA action and are generally grouped into two classes, D1-like and D2-like receptors. Unlike Drosophila, which uses histamine as a neurotransmitter in photoreceptors, C. elegans does not use histamine, creating an interesting point of divergence in both systems. Histamine receptors act in photoreceptors to synchronize flies’ behavioral rhythms with light-dark cycles. Here, we review the comprehensive set of known amine neurotransmitters found in invertebrates, and discuss their biological and modulatory functions using the vast knowledge cataloged in C. elegans and Drosophila. We also suggest implications of the interaction among these neurotransmitters for the modulation of physiology and behavior.